The application of exosomes in the early diagnosis and treatment of osteoarthritis - Chen, Anjing; Chen, Yangmengfan; Rong, Xiao; You, Xuanhe; Wu, Diwei; Zhou, Xinran; Zeng, Weinan; Zhou, Zongke (Frontiers in Pharmacology, 2023)
With the increase in human lifespan and the aggravation of global aging, the incidence of osteoarthritis (OA) is increasing annually. To better manage and control the progression of OA, prompt diagnosis and treatment for early-stage OA are important. However, a sensitive diagnostic modality and therapy for early OA have not been well developed. The exosome is a class of extracellular vesicles containing bioactive substances, that can be delivered directly from original cells to neighboring cells to modulate cellular activities through intercellular communication. In recent years, exosomes have been considered important in the early diagnosis and treatment of OA. Synovial fluid exosome and its encapsulated substances, e.g., microRNA, lncRNA, and proteins, can not only distinguish OA stages but also prevent the progression of OA by directly targeting cartilage or indirectly modulating the immune microenvironment in the joints. In this mini-review, we include recent studies on the diagnostic and therapeutic modalities of exosomes and hope to provide a new direction for the early diagnosis and treatment of OA disease in the future.